Media Relations Strategy for Tin Mining Companies and Agenda Setting Media in Bangka Belitung - Ortega, Aditia; Lani, Rama Dwi Putri (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
This paper describes the media relations strategy used by tin mining companies in Bangka Belitung province in developing the media setting agenda. On the one hand, tin mining companies have an agenda so they can carry out mining according to regulations. On the other hand, the local government as a party outside the mass media institutions and mining companies also has its own agenda. So that the issue of tin mining in Bangka Belitung has the potential for conflict of interest, not only between companies and the government, but also with community members. This study aims to find out how the media relations strategy of tin mining companies is in compiling the agenda setting of the mass media in Bangka Belitung. This is a qualitative research with data collection techniques through participatory observation. The research data was obtained through semi-closed observation and participation as well as interviews with a number of informants who have competence and relevance to the research problem. The findings of this study indicate that the mass media as an economic institution is driven by transactional principles. On the other hand, tin mining companies and local governments have a common agenda setting. The relationship between these various sides is an internal factor that occurs in a very dynamic new media climate. While the very dynamic activity in the new media era is an external factor. The relationship between internal and external factors is described as something that can set the media setting agenda. Agenda setting is a theory that explains the media shape the audience's agenda